2020
DOI: 10.1111/ppl.13221
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic variation in intrinsic transpiration efficiency correlates with sugarcane yield under rainfed and irrigated field conditions

Abstract: Intrinsic transpiration efficiency ( i TE), the ratio of photosynthesis (A) to stomatal conductance (g s ), is considered a useful trait for improving productivity; however, higher i TE with high A is more desirable than that with low g s . This study dissects i TE of 20 sugarcane genotypes to understand its relationship with total dry matter (TDM)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…We consider that TE is a physiologically complex trait that depends on multiple physiological parameters, including photosynthesis, stomatal conductance, mesophyll conductance (i.e., the diffusion of CO 2 from sub-stomatal cavities to the sites of carboxylation in the chloroplasts) (Flexas et al, 2008;Flexas & Medrano, 2002), and other conditions that determine carbon balance and growth in plants (Natarajan et al, 2021). As a result, the conditions responsible for high TE in one situation may be associated with a low TE in another environment (Sinclair, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…We consider that TE is a physiologically complex trait that depends on multiple physiological parameters, including photosynthesis, stomatal conductance, mesophyll conductance (i.e., the diffusion of CO 2 from sub-stomatal cavities to the sites of carboxylation in the chloroplasts) (Flexas et al, 2008;Flexas & Medrano, 2002), and other conditions that determine carbon balance and growth in plants (Natarajan et al, 2021). As a result, the conditions responsible for high TE in one situation may be associated with a low TE in another environment (Sinclair, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This finding contradicts the proposal that higher TE is critical in increasing crop yields in water-limited environments (Christy et al, 2018, Sinclair, 2012, Rebetzke et al, 2002, Coupel-Ledru et al, 2016, Condon et al, 2004, Vadez and Ratnakumar, 2016). However, TE is a physiologically complex trait that results from a combination of multiple physiological parameters, such as photosynthesis, stomatal conductance, mesophyll conductance (i.e., the diffusion of CO 2 from sub-stomatal cavities to the sites of carboxylation in the chloroplasts) (Flexas and Medrano, 2002, Flexas et al, 2008), and other conditions that determine carbon balance and growth in plants (Natarajan et al, 2021). Consequently, the conditions responsible for the expression of high TE in one situation may be associated with a low TE in another environment (Sinclair, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that drought has a drastic effect on photosynthetic traits, such as net photosynthetic rate [14,15,17]. Low soil moisture and high air temperature generally occur together, and drought leads to evapotranspiration and affects photosynthesis under field conditions [47].…”
Section: Effect Of Drought Stress On Photosynthetic Parameters Under Drought and Recovery Conditionsmentioning
confidence: 99%
“…It is affected not only by the decline of stomatal conductance but also by the level of chloroplast damage under severe stress [11][12][13]. The net photosynthetic rates and stomatal conductance of sugarcane leaves decline after exposure to drought [14][15][16]. The tolerant sugarcane cultivars exhibited better photosynthetic performance than the sensitive cultivar [17].…”
Section: Introductionmentioning
confidence: 99%